Polynomials play an important role in algebra and calculus. A polynomial equation is the equation of degree n which has exactly n roots. The remainder theorem provides insights into polynomial division and equations. Further, a remainder theorem has numerous applications in physics, engineering, astronomy, etc.
JEE Main 2025: Sample Papers | Mock Tests | PYQs | Study Plan 100 Days
JEE Main 2025: Maths Formulas | Study Materials
JEE Main 2025: Syllabus | Preparation Guide | High Scoring Topics
In this article, we will cover the concept of polynomial equation of higher degree and Remainder Theorem. This concept falls under the broader category of complex numbers and quadratic equations, a crucial Chapter in class 11 Mathematics. It is not only essential for board exams but also for competitive exams like the Joint Entrance Examination (JEE Main), and other entrance exams such as SRMJEE, BITSAT, WBJEE, BCECE, and more.
An expression of the form $f(x)=a_0 x^n+a_1 x^{n-1}+a_2 x^{n-2}+\ldots+a_{n-1} x+a_n$, is called a polynomial expression.
Where $x$ is variable and $a_0, a_1, a_2, \ldots \ldots . ., a_n$ are constant, known as coefficients and $a_0 \neq 0, n$ is non-negative integer,
Degree: The highest power of the variable in the polynomial expression is called the degree of the polynomial. In $a_0 \cdot x^n+a_1 \cdot x^{n-1}+\ldots+a_n$ , the highest power of x is n, so the degree of this polynomial is n.
If coefficients are real numbers then it is called a real polynomial, and when they are complex numbers, the polynomial is called a complex polynomial.
If $\mathrm{f}(\mathrm{x})$ is a polynomial, $\mathrm{f}(\mathrm{x})=0$ is called a polynomial equation.
The value of x for which the polynomial equation, $\mathrm{f}(\mathrm{x})=0$ is satisfied is called a root of the polynomial equation.
If $x=a$ is a root of the equation $f(x)=0$, then $f(a)=0$.
Eg, $x=2$ is a root of $x^2-3 x+2=0$, as $x=2$ satisfies this equation.
A polynomial equation of degree n has n roots (real or imaginary).
An equation of the form $a_0 x^n+a_1 x^{n-1}+\ldots+a_{n-1} x+a_n=0$ where $\mathrm{a}_0, \mathrm{a}_1, \ldots, \mathrm{a}_{\mathrm{n}}$ are constant and $\mathrm{a}_0 \neq 0$
is known as the polynomial equation of degree n which has exactly n roots (i.e., number of real roots + number of imaginary roots = n)
sum of all roots $=\sum \alpha_1=\alpha_1+\alpha_2+\ldots+\alpha_{n-1}+\alpha_n=(-1) \frac{a_1}{a_0}$
sum of products taken two at a time
$
\sum \alpha_1 \alpha_2=\alpha_1 \alpha_2+\alpha_1 \alpha_3+\ldots+\alpha_1 \alpha_{\mathrm{n}}+\alpha_2 \alpha_3+\ldots+\alpha_2 \alpha_{\mathrm{n}}+\ldots+\alpha_{\mathrm{n}-1} \alpha_{\mathrm{n}}=(-1)^2 \frac{\mathrm{a}_2}{\mathrm{a}_0}
$
sum of products taken three at a time
$
\sum \alpha_1 \alpha_2 \alpha_3=(-1)^3 \frac{a_3}{a_0}
$
product of all roots $=\alpha_1 \alpha_2 \ldots \alpha_{\mathrm{n}}=(-1)^{\mathrm{n}} \frac{\mathrm{a}_{\mathrm{n}}}{\mathrm{a}_0}$
For example,
Suppose $\mathrm{n}=3$ and $a x^3+b x^2+c x+d=0$ is polynomial equation with a ≠ 0 and $\alpha$, $\beta$ and $\gamma$ are the roots of the equation then :
$\begin{aligned} & \alpha+\beta+\gamma=-\frac{\mathrm{b}}{\mathrm{a}} \\ & \sum \alpha \beta=\alpha \beta+\beta \gamma+\gamma \alpha=(-1)^2 \frac{\mathrm{c}}{\mathrm{a}}=\frac{\mathrm{c}}{\mathrm{a}} \\ & \alpha \beta \gamma=(-1)^3 \frac{\mathrm{d}}{\mathrm{a}}=-\frac{\mathrm{d}}{\mathrm{a}}\end{aligned}$
For the transformation of roots, we can use the same procedure we used in the case of quadratic equations.
Remainder theorem
The remainder theorem states that if a polynomial f(x) is divided by a linear function (x - k), then the remainder is f(k).
In Division,
Dividend = Divisor x Quotient + Remainder
For polynomials also we can use this theorem
$f(x)=d(x) \cdot q(x)+r(x)$
where $f(x)$ is the divisor, $d(x)$ is the divisor, $q(x)$ is the quotient and $r(x)$ is the remainder. And these 4 are polynomials
The degree of remainder $r(x)$ is always less than degree of divisor $d(x)$
Now, if divisor $d(x)$ is a linear polynomial $(x-k)$. Let $q(x)$ be the quotient, remainder $r(x)$ will be a constant value equal to $R$ :
$
f(x)=(x-k) q(x)+R
$
Now if we put $x=k$
i.e. $\quad f(k)=(k-k) q(x)+R=0+R$
$
f(k)=R
$
So, remainder is $\mathrm{f}(\mathrm{k})$, when $\mathrm{f}(\mathrm{x})$ is divided by a linear polynomial $(\mathrm{x}-\mathrm{k})$
Eg. To find remainder when $f(x)=2 x^3-3 x-4$ is divided by $(x-3)$,
Here $k=3$, So remainder will be $f(k)=f(3)=2 .(3)^3-3(3)-4=54-9-4=41$
Euler's theorem states that if $n$ and $X$ are two co-prime positive integers, then:
$
X^{\varphi(n)} \equiv 1 \quad(\bmod n)
$
where $\varphi(n)$ is Euler's totient function, defined as:
$
\varphi(n)=n\left(1-\frac{1}{a}\right)\left(1-\frac{1}{b}\right)\left(1-\frac{1}{c}\right)
$
for a natural number $n$ expressed in terms of its prime factorization as:
$
n=a^p \cdot b^q \cdot c^r
$
where $a, b, c$ are distinct prime factors of $n$, and $p, q, r$ are positive integers.
Now if $f(k)=0$, then this means that the remainder when $f(x)$ is divided by $(x-k)$ is 0.
As the remainder is 0 , so $(x-k)$ is a factor of $f(x)$
So, the factor theorem states that if $\mathrm{f}(\mathrm{k})-0$, then $(\mathrm{x}-\mathrm{k})$ is a factor of $\mathrm{f}(\mathrm{x})$.
Eg, $f(x)=x^3+3 x-4$
Now we can observe by hit and trial that $f(1)=1+3-4=0$, so $(x-1)$ is a factor of $f(x)$.
Remainder Theorem | Factor Theorem | |
Definition | The remainder theorem states that the remainder when $p(x)$ is divided by $(x-a)$ is $p(a)$. | The factor theorem states that ($x - a$) is a factor of $p(x)$ if and only if $p(a)=0$. |
---|---|---|
Application | It is used to find the remainder. | It is used to decide whether a linear polynomial is a factor of the given polynomial or not. |
Example | From the above example, the remainder when $6 x^4-x^3+2 x^2-7 x$ +2 is divided by $2 x+3$ is $203 / 4$. | Since the remainder in this example is NOT $0,2 x+3$ is NOT a factor of $6 x^4-x^3+2 x^2-7 x+2$ |
This has many important applications:
Example 1: If $2+3 i$ is one of the roots of the equation, $2 x^3-9 x^2+k x-13=0, k \in R$ then the real root of this equation:
1) does not exist.
2) exists and is equal to $\frac{1}{2}$
3) exists and is equal to $-\frac{1}{2}$
4) exists and is equal to 1
Solution
As we have learned
The sum of roots of cubic Equation -
$\alpha+\beta+\gamma=\frac{-b}{c}$
Product of roots of the cubic equation -
$\alpha \beta \gamma=\frac{-d}{a}$
- wherein
$a x^3+b x^2+c x+d=0$
is the cubic equation
As complex roots always exist as conjugates,
$\begin{aligned} & \alpha=2+3 i \\ & \beta=2-32 \\ & \gamma=? \\ & \alpha+\beta+\gamma=9 / 2 \\ & \text { and } \alpha \beta \gamma=13 / 2 \\ & (4+9) \gamma=13 / 2 \\ & \gamma=1 / 2\end{aligned}$
Hence, the answer is the option 2.
Example 2: The sum of the real roots of the equation
$\left|\begin{array}{ccc}x & -6 & -1 \\ 2 & -3 x & x-3 \\ -3 & 2 x & x+2\end{array}\right|=0$, is equal to :
1) 6
2) 0
3) 1
4) -4
Solution:
Sum of roots of cubic Equation -
$\alpha+\beta+\gamma=\frac{-b}{a}$
- wherein
$a x^3+b x^2+c x+d=0$ is the cubic equation
$\left|\begin{array}{ccc}x & -6 & -1 \\ 2 & -3 x & x-3 \\ -3 & 2 x & x+2\end{array}\right|=0$
$\begin{aligned} & \Rightarrow x \cdot(-3 x(x+2)-2 x(x-3))-(-6)(2 \cdot(x+2)-(-3)(x-3))+(-1)(2.2 x-(-3)(-3 x)] \\ & \Rightarrow x^3-7 x+6 \\ & \text { Root of equation }(-3,1,2)\end{aligned}$
So,
Sum of real root of equation$=-3+1+2=0$
Example 3: Let $\alpha, \beta$ are two roots of $x^3+p x^2+q x+r=0$ \& satisfies $\alpha \beta=-1$, if $r \neq 0$ then $r^2+p r+q \mid$equals
1) 0
2) 1
3) 2
4) 3
Solution
As we learnt in
Product of roots of cubic equation -
$\alpha \beta \gamma=\frac{-d}{d}$
- wherein
$a x^3+b x^2+c x+d=0$
is the cubic equation
$\begin{aligned} & \alpha \beta \gamma=-r \\ & \therefore \alpha \beta=-1 \Rightarrow \gamma=r \\ & \therefore \text { it will satisfy the equation } \\ & \Rightarrow r^3+p r^2+q r+r=0 \\ & \Rightarrow r^2+p r+q=-1 \\ & \therefore\left|r^2+p r+q\right|=1\end{aligned}$
Hence, the answer is the option 2.
Example 3: If $\alpha, \beta, \gamma$ are roots of $x^3-x^2-1=0$ then $\frac{\alpha+1}{\alpha}+\frac{\beta+1}{\beta}+\frac{\gamma+1}{2}$ equals
1) 2
2) 3
3) 4
4) 5
Solution
As we learnt in
Sum of product of pair of roots in cubic equation -
$\alpha \beta+\beta \gamma+\gamma \alpha=\frac{c}{a}$
- wherein
$a x^3+b x^2+c x+d=0$
is the cubic equation
$\begin{aligned} & \alpha+\beta+\gamma=1 \\ & \alpha \beta+\beta \gamma+\gamma \alpha=0 ; \alpha \beta \gamma=1 \\ & \frac{\alpha+1}{\alpha}+\frac{\beta+1}{\beta}+\frac{\gamma+1}{\gamma}=1+\frac{1}{\alpha}+1+\frac{1}{\beta}+1+\frac{1}{\gamma}=3+\frac{1}{\alpha}+\frac{1}{\beta}+\frac{1}{\gamma} \\ & 3+\frac{\alpha \beta+\beta \gamma+\gamma \alpha}{\alpha \beta \gamma}=3+\frac{0}{1}=3\end{aligned}$
Hence, the answer is the option 2.
Example 5: If $\alpha, \beta, \gamma$ are roots of $x\left(1+x^2\right)+x^2(6+x)+2=0$ then $\alpha^{-1}+\beta^{-1}+\gamma^{-1}$ equals
1) -1
2) -0.5
3) 0
4) 0.5
Solution
As we learnt in
Sum of product of pair of roots in cubic equation -
$\alpha \beta+\beta \gamma+\gamma \alpha=\frac{c}{\sigma}$
- wherein
$a x^3+b x^2+c x+d=0$
is the cubic equation
Equation becomes : $2 x^3+6 x^2+x+2=0$
$\because \alpha, \beta, \gamma$, are roots , so
$\begin{aligned} \alpha \beta+\beta \gamma+\gamma \alpha=\frac{1}{2} \text { and } \alpha \beta \gamma & =-1 \\ \therefore \frac{1}{\alpha}+\frac{1}{\beta}+\frac{1}{\gamma}=\frac{\beta \gamma+\alpha \gamma+\alpha \beta}{\alpha \beta \gamma} & =\frac{\frac{1}{2}}{-1}=\frac{-1}{2}\end{aligned}$
Hence, the answer is the option 2.
The remainder theorem states that when a polynomial p(x) is divided by (x - a), then the remainder = f(a). This can be proved by Euclid division lemma. By using this, if q(x) is the quotient and 'r' is the remainder, then p(x) = q(x) (x - a) + r. Substitute x = a on both sides, then we get p(a) = r, and hence the remainder theorem is proved.
We use it to find the remainder when p(x) is divided by a linear polynomial (ax - b),
We set ax - b = 0 and find x. Here, x = b/a.
We substitute it in p(x). Then remainder = p (b/a).
The factor theorem is the main application of the remainder theorem formula. To prove the factor theorem, we need the remainder theorem. The factor theorem says if the remainder obtained by dividing p(x) by (x - r) is 0, then (x - r) is a factor of p(x).
Chinese mathematician Sun Zi invented the remainder theorem. The complete remainder theorem was given by Qin Jiushao in 1247.
If the remainder is zero, then the remaining quotient and the divisor are the factors of the given expression.
The remainder theorem states that when a polynomial p(x) is divided by (x - a), then the remainder = f(a). This can be proved by Euclid division lemma. By using this, if q(x) is the quotient and 'r' is the remainder, then p(x) = q(x) (x - a) + r. Substitute x = a on both sides, then we get p(a) = r, and hence the remainder theorem is proved.
We use it to find the remainder when p(x) is divided by a linear polynomial (ax - b),
We set ax - b = 0 and find x. Here, x = b/a.
We substitute it in p(x). Then remainder = p (b/a).
The factor theorem is the main application of the remainder theorem formula. To prove the factor theorem, we need the remainder theorem. The factor theorem says if the remainder obtained by dividing p(x) by (x - r) is 0, then (x - r) is a factor of p(x).
Chinese mathematician Sun Zi invented the remainder theorem. The complete remainder theorem was given by Qin Jiushao in 1247.
If the remainder is zero, then the remaining quotient and the divisor are the factors of the given expression.
10 Feb'25 11:53 PM
10 Feb'25 11:50 PM
10 Feb'25 11:30 PM
10 Feb'25 09:26 PM
10 Feb'25 09:23 PM
10 Feb'25 09:16 PM
10 Feb'25 08:47 PM
10 Feb'25 08:39 PM
10 Feb'25 08:31 PM
10 Feb'25 08:26 PM